Pemberdayaan Mahasiswa dalam Meningkatkan Kesadaran Lingkungan: Pendekatan Ergonomis Kolaboratif di Sektor Peternakan - Jati, Putri Zulia; Hardianti, Sri; Sari, Resy Kumala (Faculty of Engineering University of Pahlawan Tuanku Tambusai, 2024)
This service activity aims to increase environmental awareness and encourage sustainable practices in the livestock sector through student empowerment. A collaborative approach between students and lecturers is used in designing sustainable solutions, taking into account ergonomic principles. The training was held at Pahlawan Tuanku Tambusai University, involving 45 students from the Animal Husbandry Study Program. Training materials cover best practices in environmentally friendly animal husbandry, waste management and the use of green technology. Evaluation is carried out through an online questionnaire to measure success and obtain feedback from participants. The results showed significant participation, with students actively involved in discussions and field practice. The evaluation concluded that empowering students in this project succeeded in increasing environmental understanding and encouraging the adoption of sustainable practices in the livestock sector. This approach reflects a commitment to achieving sustainable development by paying attention to ergonomic aspects and intergenerational collaboration.